The Impact of Foreign Direct Investment on the Ecological Footprints of Nations - Doytch, Nadia (Archīum Ateneo, 2020)
We study the effects of foreign direct investment (FDI) on the rate of exhaustion of bioproductive physical land. We test for differential ecological performance of FDI in developed vs. developing countries, as well as in “clean” vs. “dirty” sectors. We examine the impact of six sector-level FDI flows on four ecological footprints (EF): Consumption EF, Production EF, Imports EF, and Exports EF, compiled by the Global Footprint Network. We estimate a dynamic panel model incorporating an Environmental Kuznets Curve (EKC) and differentiating across country development levels. The findings are intriguing. First, High Income countries tend to experience a consumption-related ecological impact of FDI, whereas Low- and Middle-Income countries tend to experience a production-related ecological impact of FDI. Second, the burden of FDI-generated Exports EF is born disproportionately by Middle Income countries; High Income countries bear none (evidence of FDI ecological haven). Third, in High Income countries, financial services FDI reduces the Production EF (evidence of FDI ecological halo). Finally, non-financial services FDI is more ecologically damaging than manufacturing FDI.